The Application Two-Way of Analysis of Variance with Gender and Years Class - Junaidi Junaidi; Akhmad Asyari; Ulfa Lu’luilmaknun; Nilza Humaira Salsabila; Ratna Yulis Tyaningsih (AlphaMath : Journal of Mathematics Education, 2021)
Every year the admission of new students with various backgrounds implies that students have different abilities. The difference in student abilities corresponding to student learning habits. Student learning habits maybe different if viewed from the gender and student's years class. Based on differences of student abilities is necessary to conduct research to determine the relationship between student's years class and gender toward student learning habits. This study was an ex post facto study with a sample of 203 students as the sample was selected by simple random sampling technique. Based on analysis of variance statistical analysis of two paths obtained by students' learning habits do not different in terms of gender this can be seen from Fscore = 0.008 with sig = 0.93 > 0.05, while students' learning habits are different if viewed from the year of the student's class this can be seen of the value Fscore = 3.537 with sig = 0.008 < 0.05. Post hoc test indicated that students’ 10th semester difference with student 4th semester and 2th semester. Students 2th semester difference with 6th semester and 8th semester.